Penggunaan Metode Eksperimen Untuk Meningkatkan Hasil Belajar IPA Materi Sistem Pernafasan Manusia Pada Kelas V SD Kristen Pupliora: Indonesia - Nawaly, Angly; Umarella, Melati I.S. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the improvement in science learning outcomes for fifth grade student at Kristen Pupliora Elementary school. On the subject of the human respiratory system using an experimental learning model. This research is classroom action research. The research location used in this Kristen Pupliora elementary school. The subject in this research were sixteen fifth grade students at Kristen Pupliora elementary school. The results of the research show that use of experimental methods in fifth grade students at Kristen Pupliora elementary school shows a significant increase in learning outcomes which is marked by achieving learning completeness in science subjects. This can be seen from the percentage of completion in the pre-cycle of 6%, then in cycle it wa 12%, and in cycle it increased to 94%.